Make It Real (to Me) - Roston, Miles (Film Victoria ; Australian Film Commission ; International Production Services Australia, 2005)
Verzio FF Submission Kevin is an orphan and has been since the age of ten. He lives in Kisumu, Kenya where both his parents died of AIDS. Now seventeen, he knows his chances for survival are slim as where he lives forty percent of girls his age are HIV positive. Determined to make a difference, Kevin makes an incredible journey, not only encountering other orphans like himself, elders and the Mayor of his town, but venturing across the land to the halls of power in the capital, challenging top industrialists, religious leaders, and even the Vice President. This is the story of a young man's courage, inspiring others like him to bring about change, set against the background of the AIDS epidemic and the turmoil of Africa.